2024
DOI: 10.1101/2024.04.26.590643
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An integrated single-nucleus and spatial transcriptomics atlas reveals the molecular landscape of the human hippocampus

Jacqueline R. Thompson,
Erik D. Nelson,
Madhavi Tippani
et al.

Abstract: The hippocampus contains many unique cell types, which serve the structure's specialized functions, including learning, memory and cognition. These cells have distinct spatial topography, morphology, physiology, and connectivity, highlighting the need for transcriptome-wide profiling strategies that retain cytoarchitectural organization. Here, we generated spatially-resolved transcriptomics (SRT) and single-nucleus RNA-sequencing (snRNA-seq) data from adjacent tissue sections of the anterior human hippocampus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 198 publications
0
10
0
Order By: Relevance
“…Nmf patterns generated from one dataset can predict the presence and distribution of these same latent factors in another dataset via transfer learning 58 . This strategy was recently used to integrate snRNA-seq and Visium data from adult neurotypical donors in HPC 59 . Specifically, 100 nmf patterns were identified in snRNA-seq data from which we identified three patterns (nmf26, nmf5, and nmf14) that were enriched in GC populations with a sequential overlap of weight gradients where nmf26 partially overlaps with nmf5, which partially overlaps with nmf14 ( Figure 4a ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nmf patterns generated from one dataset can predict the presence and distribution of these same latent factors in another dataset via transfer learning 58 . This strategy was recently used to integrate snRNA-seq and Visium data from adult neurotypical donors in HPC 59 . Specifically, 100 nmf patterns were identified in snRNA-seq data from which we identified three patterns (nmf26, nmf5, and nmf14) that were enriched in GC populations with a sequential overlap of weight gradients where nmf26 partially overlaps with nmf5, which partially overlaps with nmf14 ( Figure 4a ).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, 100 nmf patterns were identified in snRNA-seq data from which we identified three patterns (nmf26, nmf5, and nmf14) that were enriched in GC populations with a sequential overlap of weight gradients where nmf26 partially overlaps with nmf5, which partially overlaps with nmf14 ( Figure 4a ). Projecting these three patterns onto paired SRT data from the same donors 59 revealed that, although all three patterns were restricted to the GCL ( Figure 4b ), nmf26 weights were more sparsely distributed. We thus compared the top 10 marker genes for these three patterns to better understand the biological relevance ( Figure 4c ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations